2020
DOI: 10.1186/s12985-020-01414-x
|View full text |Cite
|
Sign up to set email alerts
|

RNA silencing-related genes contribute to tolerance of infection with potato virus X and Y in a susceptible tomato plant

Abstract: Background In plants, the RNA silencing system functions as an antiviral defense mechanism following its induction with virus-derived double-stranded RNAs. This occurs through the action of RNA silencing components, including Dicer-like (DCL) nucleases, Argonaute (AGO) proteins, and RNA-dependent RNA polymerases (RDR). Plants encode multiple AGOs, DCLs, and RDRs. The functions of these components have been mainly examined in Arabidopsis thaliana and Nicotiana benthamiana. In this study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 73 publications
(117 reference statements)
0
12
0
Order By: Relevance
“…Regarding the low accumulation of PSTVd in wild tomato relatives, it is possible that PSTVd replication and intercellular/systemic transfer were suppressed or that the accumulated PSTVd was degraded by the anti-viroid defense mechanism, including RNA silencing. In previous reports, suppression of DCL2 and DCL4 in tolerant ‘Moneymaker’ tomatoes increased the accumulation and sensitivity during PSTVd, PVX, or PVY infection [ 46 , 47 ]. It has also been reported that the combined activity of DCL2 and DCL3 in N. benthamiana is important for suppressing the disease symptom expression of PSTVd [ 48 ].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the low accumulation of PSTVd in wild tomato relatives, it is possible that PSTVd replication and intercellular/systemic transfer were suppressed or that the accumulated PSTVd was degraded by the anti-viroid defense mechanism, including RNA silencing. In previous reports, suppression of DCL2 and DCL4 in tolerant ‘Moneymaker’ tomatoes increased the accumulation and sensitivity during PSTVd, PVX, or PVY infection [ 46 , 47 ]. It has also been reported that the combined activity of DCL2 and DCL3 in N. benthamiana is important for suppressing the disease symptom expression of PSTVd [ 48 ].…”
Section: Discussionmentioning
confidence: 98%
“…Cucumber mosaic virus strain yellow (CMV-Y) and PVY strains N and O (PVY N and PVY O ) ( Kwon et al, 2020 ) were initially propagated on Nicotiana benthamiana , and infected upper leaves were used as inoculum for mechanical inoculation. Tomato seedlings at the second or third true leaf stage were mechanically inoculated with crude inoculum, which was viral-infected leaf tissue ground in 0.1 M phosphate buffer (pH 7.0).…”
Section: Methodsmentioning
confidence: 99%
“…Following the time-course observations of symptom expression, viral coat protein (CP) accumulation in non-inoculated upper leaves at 25 or 35 days post inoculation (dpi) was investigated with a double antibody sandwich-enzyme linked immunosorbent assay (ELISA) using anti-CP polyclonal antibody (Japan Plant Protection Association). Reverse transcription PCR (RT-PCR) analysis to detect CMV-Y genomic RNA was performed with a pair of primers, 5'-gtacagagttcagggttgagcg-3' and 5'-agcaatactgccaactcagctcc-3', as described in our previous study ( Kwon et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…1 The proportion of BrYV P0∆235-249 detected in the inoculated leaves at 2 dpi. 2 The proportion of BrYV P0∆235-249 detected in the upper leaves at 14 dpi. 3 The proportion of successful systemic infections by BrYV P0∆235-249 .…”
Section: The Mutant Bryvmentioning
confidence: 99%
“…RNA silencing is a natural host antiviral defense pathway at the nucleic acid level [1,2]. It occurs through the processing of double-stranded RNAs into complementary short (21-24 nucleotides) interfering RNAs (siRNAs) by the Dicer-like enzyme RNAse III [3,4].…”
Section: Introductionmentioning
confidence: 99%